Insights into host-pathogen interaction based on the comparison of genomes of Leptospira interrogans isolated from dogs, humans, and a rodent in the same epidemiological context: A one health approach - Lucas Nogueira Paz; Laise de Moraes; Luciane Amorim Santos; Camila Hamond; Melissa Hanzen Pinna (Heliyon)
Leptospirosis is a zoonotic infectious disease that significantly impacts animal and public health. Comparative genomics can aid in understanding poorly understood aspects of leptospirosis pathogenesis, including infection mechanisms, antimicrobial resistance, and host interactions across different epidemiological scenarios. This study aimed to compare the genomes of Leptospira interrogans serogroup Icterohaemorrhagiae strains isolated from three host species in a single epidemiological scenario. Four strains of L. interrogans serogroup Icterohaemorrhagiae from naturally infected and clinically symptomatic dogs (C20, C29, C51, and C82) were processed for whole genome sequencing (WGS). These results were compared against WGS data from two other rodent and human strains. Phylogenetic and genomic similarity analyses demonstrated high identity and synteny between the strains isolated from humans, canines, and rodents. Small regions of divergence were observed, especially in the genome obtained from a rodent sample. The presence of 23 genes potentially associated with biofilm formation was notable, with the identification of missense mutations in eight genes. Considering the need to better understand the molecular basis involved in biofilm formation, it is of fundamental importance to elucidate the effect of mutations on the expression of the phenotype (biofilm) among different strains. The present findings highlight the necessity of One Health-based collaborative interventions to address the complex dynamics of leptospirosis transmission, involving both common hosts such as rodents and dogs, as well as less-recognized hosts.